2021
DOI: 10.1108/jsit-02-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

E-learning satisfaction and retention: a concurrent perspective of cognitive absorption, perceived social presence and technology acceptance model

Abstract: Purpose The purpose of this study is to concurrently test the effect of cognitive absorption and perceived social presence on technology acceptance model core variables, e-satisfaction and e-retention among undergraduate students of Northern Malaysian public universities. Design/methodology/approach To empirically test the model, the authors developed quantitative research by collecting data from 730 undergraduate students of public universities in the Northern states of Malaysia. Partial least squares–struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 72 publications
5
26
0
7
Order By: Relevance
“…Another paper, by Léger et al (2014), studied 36 students, and concluded that cognitive absorption has a significant effect on the learning outcomes. Therefore, scholars have found in e-learning systems a close association between the PCA and the intention to continue use, as in the study by Venter and Swart (2018) on a computer science undergraduate programme in South Africa on learning simulation modelling and as in the study of 730 undergraduate students in Malaysia who used an e-learning platform (Salimon et al, 2021). On the same lines, the present study proposes that improving the learner's PCA will accordingly intensify the CIU.…”
Section: H1: Psrl Positively Affects Ciusupporting
confidence: 50%
See 1 more Smart Citation
“…Another paper, by Léger et al (2014), studied 36 students, and concluded that cognitive absorption has a significant effect on the learning outcomes. Therefore, scholars have found in e-learning systems a close association between the PCA and the intention to continue use, as in the study by Venter and Swart (2018) on a computer science undergraduate programme in South Africa on learning simulation modelling and as in the study of 730 undergraduate students in Malaysia who used an e-learning platform (Salimon et al, 2021). On the same lines, the present study proposes that improving the learner's PCA will accordingly intensify the CIU.…”
Section: H1: Psrl Positively Affects Ciusupporting
confidence: 50%
“…Since the PCA can improve the effective use of applications (Moreno et al, 2016). Similarly, Salimon et al (2021) found that the PCA affects the perception of usefulness of the e-learning platform. Taking this approach to deduction, it can be extrapolated that the PCA from using LMS positively affects the PLSR from it.…”
Section: H2: Pca Positively Affects the Ciumentioning
confidence: 90%
“…Researchers also used the technology acceptance model (TAM) to measure the satisfaction of e-learning. Specific hypotheses were tested and evaluated for the quality and effectiveness of e-learning (Salimon et al, 2021). Other researchers use the value-based adoption model (VAM), which measures the acceptance of e-learning (Al-Maroof et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, there are existing studies that confirm the technology-related characteristics of participants through the relationship between TR and the TAM [42][43][44][45][46]. Furthermore, there are studies that have affirmed the relationship between technology acceptance and SP [47,48], but the context is limited to e-learning or distance learning. These existing studies, which integrate the TAM and TR perspectives, indicate that a positive attitude toward the technology of virtual meeting platforms leads to stronger experiences of ease of use and usefulness, stronger engagement with the course, and a stronger experience of SP during the course.…”
Section: Technology Readiness Social Presence Course Satisfaction And...mentioning
confidence: 99%